2020
DOI: 10.1186/s13002-020-00380-6
|View full text |Cite
|
Sign up to set email alerts
|

Bear bile use at the intersection of maternal health in Cambodia

Abstract: Background: The consumption of bear gallbladders and bear bile in Southeast Asia is a persistent threat to bear populations. As part of a larger effort to understand the characteristics of bear part consumption in Cambodia, we uncovered a consumer base of women seeking treatment for post-partum and uterine ailments. Methods: To better understand this aspect of consumption, we interviewed 122 women in seven different provinces in Cambodia, probing into the motivations and influences for using bear bile, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 30 publications
5
14
0
Order By: Relevance
“…For a time frame of 12 months, the highest level of use was estimated at being about 25% of the sample (with significant variability) for unmatched count technique (UCT) in Koh Kong, and the lowest estimate at 0% in neighbouring Kampong Speu Province (although this result likely indicated that substantial deceit occurred in the sample; Figure 5a). We found that bear bile was used for fevers, and confirmed prior research that found the use of bear bile for pregnancy and postpartum ailments (Davis et al, 2020). For example, a 50-year-old Khmer woman in Preah Vihear said:…”
Section: Bear Bile Consumption Prevalencesupporting
confidence: 85%
See 2 more Smart Citations
“…For a time frame of 12 months, the highest level of use was estimated at being about 25% of the sample (with significant variability) for unmatched count technique (UCT) in Koh Kong, and the lowest estimate at 0% in neighbouring Kampong Speu Province (although this result likely indicated that substantial deceit occurred in the sample; Figure 5a). We found that bear bile was used for fevers, and confirmed prior research that found the use of bear bile for pregnancy and postpartum ailments (Davis et al, 2020). For example, a 50-year-old Khmer woman in Preah Vihear said:…”
Section: Bear Bile Consumption Prevalencesupporting
confidence: 85%
“…Vihear and Siem Reap, as supported by the GLM (Table 3) and Figure 5, while our finding that Stung Treng individuals are using bear bile at a higher rate than other areas in Cambodia ( Figure 5) corroborates both the GLM (Table 3) 6 months is about 5%. This reflects previous findings that use of bear bile in Cambodia, although common over time, is a relatively rare occurrence when considered even at the annual scale, since it is most often utilized in specific and traumatic incidents such as poor health following pregnancy (Davis et al, 2020), and/or to treat bruising and broken bones after a traffic accident (Davis, 2019). Therefore, the use of bear bile will more generally reflect the prevalence of traumatic incidents interacting with propensity to use.…”
Section: The Use Of Bear Bile Was Significantly Less Prevalent In Preahsupporting
confidence: 80%
See 1 more Smart Citation
“…This caused participants to depend heavily on self‐diagnosis and personal opinion when treating themselves and their family. This observation is supported by other research (Lim et al., 2005), and links to anthropological literature around female kin networks and how access to, and reliance on, these networks has impacts on women's health (Davis et al., 2020).…”
Section: Design Process Overview and Inputssupporting
confidence: 77%
“…In addition, the effectiveness of a medicinal treatment can also be conceptually extended to include not only its physical effects but also the impacts it has on an individual's social placement (c.f. Davis et al., 2020), which may factor into their internal processing.…”
Section: Target Audience Influences (Step 4)mentioning
confidence: 99%